2021
DOI: 10.1002/jhet.4283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of julolidines via one‐pot cascade three component Povarov reaction in the presence of silica sulfuric acid

Abstract: In this report, synthesis of julolidines via one‐pot cascade reaction of aniline derivatives with a mixture of styrene and formaldehyde in the presence of silica sulfuric acid as an efficient catalyst has been studied under aerobic condition. By presented method, various julolidines are obtained under mild and transition metal‐free conditions. The reaction is proceeded with imine formation and followed by an Aza‐Diels‐Alder cycloaddition with styrene gave julolidine derivatives. The catalyst can be recycled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, the easy workup procedure allowed the organocatalyst to be reused up to four times without relevant loss of catalytic activity. The synthesis of julolidines through the one-pot cascade reaction of aniline derivatives 219 with a mixture of styrene (220) and formaldehyde (195) using silica sulfuric acid (SSA) as catalyst has also been reported (Scheme 52) [140]. Reactions were carried out in water under refluxing conditions for 24 h and led to the desired products 221 as diastereoisomeric mixtures in moderate to good yield.…”
Section: Catalyzed Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the easy workup procedure allowed the organocatalyst to be reused up to four times without relevant loss of catalytic activity. The synthesis of julolidines through the one-pot cascade reaction of aniline derivatives 219 with a mixture of styrene (220) and formaldehyde (195) using silica sulfuric acid (SSA) as catalyst has also been reported (Scheme 52) [140]. Reactions were carried out in water under refluxing conditions for 24 h and led to the desired products 221 as diastereoisomeric mixtures in moderate to good yield.…”
Section: Catalyzed Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
“…Reactions were carried out in water under refluxing conditions for 24 h and led to the desired products 221 as diastereoisomeric mixtures in moderate to good yield. When o-substituted anilines were used, tetrahydroquinolines 222 were obtained, although the increase in reaction time (48 h) The synthesis of julolidines through the one-pot cascade reaction of aniline derivatives 219 with a mixture of styrene (220) and formaldehyde (195) using silica sulfuric acid (SSA) as catalyst has also been reported (Scheme 52) [140]. Reactions were carried out in water under refluxing conditions for 24 h and led to the desired products 221 as diastereoisomeric mixtures in moderate to good yield.…”
Section: Catalyzed Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
“…Recently, in 2021, Kaboudin et al 202 reported the synthesis of julolidines 108 by utilizing silica sulfuric acid (SSA) as a recoverable and reusable heterogeneous catalyst, anilines 2 , styrene ( 65 ) as the alkene, and formaldehyde ( 87 ) (Scheme 28 ). In total, six julolidines were obtained in yields of 51–78%.…”
Section: Julolidinesmentioning
confidence: 99%
“…A double Povarov reaction has been also considered to synthesize julolidine derivatives employing TFA, TFE, 36 silica sulphuric acid and p-sulfonic acid calix [4] arene as catalysts. 37,38 However, a more well-designed and developed methodology to construct these polycyclic structures involves the use of functional amines, aldehydes or dienophiles which can undergo consecutive reactions in a one-pot fashion. Following this approach, a series of furo [3,2-c]pyrrolo[1,2-a] quinoline derivatives were obtained starting from homopropargylic amines which undergo an intramolecular hydroamination and cycloisomerization forming a 2-azadiene which react with electron-rich olens.…”
Section: Introductionmentioning
confidence: 99%